RELIGIUSITAS SISWA MADRASAH ALIYAH DAN SEKOLAH MENENGAH ATAS - Iyoh Mastiyah (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
AbstractThis article is written based on the research conducted amongst the students of Madrasah Aliyah Negeri 2 (equivalent to Public Senior High School) and Public Senior High School 3 in Bogor. This research was carried out by using quantitative approach, with the parameter on religiosity aspects (knowledge, internalizing, belief, ritual worship behaviour, social behaviour, and attitude to anticipate negative behaviour). The findings showed that the religiosity level of the students in MAN 2 is higherÂ than in SMAN 3. Belief is an aspect that had significant influence in decreasing negative behaviour. Meanwhile, internalizing is a significant aspect to increase religious practice and social behaviour. However, knowledge is an aspect that does not directly influence ritual behaviour (worship), social behaviour, and attitude to anticipate negative behaviour. These findings explained the necessity to improve the teaching of religious education, which is more oriented in building religious belief and internalizing, than merely building knowledge.Keywords: Madrasah Aliyah; Senior High School; Studentâ€™s ReligiosityAbstrak Tulisan ini merupakan hasil penelitian yang dilakukan terhadap siswa Madrasah Aliyah Negeri 2 dan Sekolah Menengah Atas Negeri 3 di Kota Bogor. Penelitian ini menggunakan pendekatanÂ kuantitatif dengan fokus pengukuran pada dimensi religiusitas (pengetahuan, penghayatan, keyakinan, praktik ritual keagamaan, perilaku sosial dan perilaku menghindari perbuatan negatif). Temuan penelitian menunjukan siswa MAN 2 mempunyai tingkat religiusitas (aspek pengetahuan, keyakinan, penghayatan, dan perilaku ibadah) lebih tinggi dibandingkan SMAN 3. Dimensi keyakinan mempunyai pengaruh signifikan dalam menurunkan perilaku negatif sedangkan dimensi yang signifikan untuk meningkatkan praktik ibadah dan perilaku sosial adalah penghayatan. Sebaliknya dimensi pengetahuan tidak mempengaruhi secara langsung terhadap perilaku ritual (ibadah), perilaku sosial dan perilaku menghindari hal negatif. Temuan ini menunjukan perlunya peningkatan pengajaran pendidikan agama yang lebih berorientasi pada pembentukan keyakinan dan penghayatan keagamaan dibandingkan pembentukan pengetahuan semata.